Predictors of financial hardship among single mothers in Peninsular Malaysia - Mat Rahim, Fatin Farwizah (2022)
Financial hardship remains a significant problem among the vulnerable groups, especially single mothers. The financial hardship may be contributed by various factors, including personality traits, materialism, stress and single mothers’ behaviours. Therefore, this study investigated the predictors of single mothers’ financial hardship related to the conscientiousness trait, materialism, stress, compulsive buying behaviour and savings behaviour. The Resource Management Model of Stress, the Escape Theory and the Prospect Theory was applied as the primary theoretical background of the study. Following that, a conceptual framework was developed to identify the influence of the conscientiousness trait, materialism and stress on single mothers’ financial hardship. The conceptual framework also included the mediating effect of compulsive buying behaviour and savings behaviour in the influence of the exogenous variables on single mothers’ financial hardship. Additionally, this study examined the moderating effect of income groups to assess the differential effects of income groups on the influence between the exogenous variables and single mothers’ financial hardship. Multi-stage random sampling was utilised to collect data from 450 single mothers in four zones in Peninsular Malaysia which is represented by four states, namely Perak, Selangor, Pahang and Melaka. The self-administered questionnaire was distributed to the single mothers through the randomly selected registered single mothers’ associations. A total of 407 usable data was retained for further analysis. In this study, the data was statistically analysed for descriptive analysis and Structural Equation Modelling with a relatively good model fit. The findings revealed a significant influence of stress, compulsive buying behaviour and savings behaviour on single mothers’ financial hardship. An indirect mediation effect of compulsive buying behaviour was found in the influence of conscientiousness traits and materialism on financial hardship, meanwhile, partial mediation was depicted in the influence of stress on financial hardship. However, no mediation effect of savings behaviour was demonstrated in the influence between the exogenous variables and financial hardship. Furthermore, a moderation effect of income groups between below hard-core PLI and above hard-core PLI was found in the influence of savings behaviour on financial hardship. This study appeared to support the importance of assessing single mothers’ conscientiousness trait, materialism and stress factors, and behaviours that can predict their financial hardship. The empirical evidence suggested a social policy that promotes financial education for single mothers. Furthermore, single mothers should also be educated on stress management in an effort to manage and reduce their stress accordingly. This study also emphasised some research implications and recommendations for future studies of financial hardship and single mothers.